The Effect of Return on Assets, Current Ratio, Debt to Equity Ratio on Tax Avoidance with Capital Intensity as a Moderating Variable (Empirical Study on Property and Real Estate Companies Listed on the Indonesia Stock Exchange in 2020-2023) - Christy, Dian; Nurhasanah, Nurhasanah (Countable (Contemporary Business and Sustainability Science), 2024)
The purpose of this study is to examine how return on assets, current ratio, and debt to equity ratio affect tax avoidance efforts, by considering the capital intensity variable as a moderating factor. The variables used in this study are return on asset, current ratio, and debt to equity ratio. The variable that will be analyzed in this study is tax avoidance. The moderation variable in this study is capital intensity. In this study, the data used came from the official website of the Indonesia Stock Exchange. The study population consists of 92 property and real estate companies listed on the Indonesia Stock Exchange from 2020-2023. The study used the purposive sampling method to select 23 companies as a sample. The data analysis method in this study uses panel data regression analysis and moderation regression analysis using eviews 12 software. The results show that return on assets have a negative effect on tax avoidance, but the current ratio and debt to equity ratio do not affect tax avoidance. Capital intensity is proven to reduce the influence of return on asset, current ratio, and debt to equity ratio on tax avoidance.